Tooth Contact Analysis of Cycloidal Pinwheel Drive in RV Reducer of Robot - Liang Shuaifeng; Deng Xiaozhong; Li Tianxing; Wang Changlu; Yang Jingzhao (Jixie chuandong)
The second-stage drive of the RV reducer,cycloidal pinwheel drive is taken as the research object. By analyzing the motion relationship of the cycloidal pinwheel drive,the tooth contact analysis（TCA）model is established. Based on the gear meshing principle and the condition for the continuous contact of the gear,the TCA equations are established. The difficulty of solving the initial reference points in the TCA calculation is described. The instantaneous meshing state,the meshing area and the transmission error of the cycloidal pinwheel drive with the traditional modification are solved. And then the return error is also solved. This method will provide a theoretical basis for the loaded tooth contact analysis of the cycloidal pinwheel drive.